METHOD OF IMPROVING ENERGY, ECOLOGICAL AND STENGTH CHARACTERISTICS OF THE VEHICLE DIESEL ENGINE - Abramchuk, F.; Makovyey, R.; Avramenko, A.; Абрамчук, Ф. И.; Маковей, Р. Г.; Авраменко, А. Н.; Абрамчук, Ф. І.; Авраменко, А. М. (Харьковский национальный автомобильно-дорожный университет, 2016)
The article deals with a complex method of deterioration of economic, ecological, and strength indicators of 16ЧН26/27 transport diesel engine. According to the offered method, there were considered conjugated problems applicable to the transport diesel engine combustion chamber and cooling cavities of the cylinder head. Based on the complex research conducted.
МЕТОДИКА СОВЕРШЕНСТВОВАНИЯ ЭНЕРГО-ЭКОЛОГИЧЕСКИХ И ПРОЧНОСТНЫХ ПОКАЗАТЕЛЕЙ ТРАНСПОРТНОГО ДИЗЕЛЯ
МЕТОДИКА ВДОСКОНАЛЕННЯ ЕНЕРГО-ЕКОЛОГІЧНИХ ТА МІЦНІСНИХ ПОКАЗНИКІВ ТРАНСПОРТНОГО ДИЗЕЛЯ
Keywords: diesel engine; conjugated problem; level of strains; finite element method; дизель; сопряженная задача; уровень напряжений; метод конечных элементов; дизель; спряжена задача; рівень напружень; метод скінчених елементів; 621. 43